2009
DOI: 10.1104/pp.109.141994
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Reactive Oxygen Species and NADPH Oxidase RBOHD in an Arabidopsis-Alternaria Pathosystem

Abstract: Arabidopsis (Arabidopsis thaliana) NADPH oxidases have been reported to suppress the spread of pathogen- and salicylic acid-induced cell death. Here, we present dual roles of RBOHD (for respiratory burst oxidase homolog D) in an Arabidopsis-Alternaria pathosystem, suggesting either initiation or prevention of cell death dependent on the distance from pathogen attack. Our data demonstrate that a rbohD knockout mutant exhibits increased spread of cell death at the macroscopic level upon inoculation with the fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
158
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(168 citation statements)
references
References 83 publications
9
158
1
Order By: Relevance
“…It is possible that the decreased nematode size results indirectly from increased plant cell death in rbohD/F plants, which would reduce the number of cells available to be included in the syncytia. Our model is compatible in part with previous findings showing that pathogen-induced ROS suppress the spread of SA-mediated cell death signals in plants after infection (16,31). It was suggested that RbohD suppresses the spread of cell death by controlling the levels of antioxidants in cells at and around the infection site (16).…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 81%
“…It is possible that the decreased nematode size results indirectly from increased plant cell death in rbohD/F plants, which would reduce the number of cells available to be included in the syncytia. Our model is compatible in part with previous findings showing that pathogen-induced ROS suppress the spread of SA-mediated cell death signals in plants after infection (16,31). It was suggested that RbohD suppresses the spread of cell death by controlling the levels of antioxidants in cells at and around the infection site (16).…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 81%
“…1A). In Arabidopsis thaliana, rbohD knockout mutant plants accumulate high levels of the defense hormone salicylic acid (SA) and show increased expression of the SA marker gene PR-1 upon pathogen challenge (33,34). However, it has been reported that The numbers below the blots represent the relative accumulation levels (means ± SD) of viral RNAs (RNA1 and RNA2, respectively) using ImageJ software (NIH), which were calculated based on three independent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The Arabidopsis RBOHD gene encoding a NADPH oxidase is crucial for ROS production in response to pathogens (Pogány et al, 2009). After flg22 treatment, the expression of RBOHD is up-regulated from 3 h after elicitation (Fig.…”
Section: Effects Of Mamps On Defense Gene Activation In Root Border-lmentioning
confidence: 99%